Does dance therapy benefit the improvement of blood pressure and blood lipid in patients with hypertension? A systematic review and meta-analysis - Wang, Jialin; Yin, Yikun; Yu, Zhengze; Lin, Qihan; Liu, Yongsheng (Frontiers in Cardiovascular Medicine, 2024)
Objective Hypertension is a risk factor of cardiovascular disease. Dance, a type of aerobic exercise, is beneficial as a therapy in reducing blood pressure. This study aimed to systematically review the therapeutic effectiveness of dance therapy (DT) on blood pressure and blood lipid of patients with hypertension. Methods Searching CNKI, VIP, Wan Fang Databases, CBM, PubMed, EBSCO (MEDLINE), Cochrane Library, and Web of Science to collect randomized controlled trials (RCTs) about dance therapy in the treatment of patients with hypertension according to the inclusion and exclusion criteria, with the search time ranged from the date of database construction to January 2024. The Cochrane risk-of-bias tool and PEDro were used to evaluate the risk of included trials. The meta-analysis was implemented by using RevMan 5.4 and Stata 12.0 software. Results A total of 983 patients were included in 11 randomized controlled trials. According to the meta-analysis, compared with the control group, Dance Therapy effectively reduced systolic blood pressure (SBP) [MD = −7.45, 95% CI (−8.50, −6.39), p < 0.0001] and diastolic blood pressure (DBP) [MD = −2.95, 95% CI (−3.78, −2.13), p < 0.0001], and it increased high-density lipoprotein cholesterol (HDL-C) [MD = 0.20, 95% CI (−0.02, 0.42), p < 0.0001]. The subgroup analysis results showed that the treatment efficacy was more excellent with the frequency more than 3 times per week, the cycle less than 12 weeks, and the duration less than 60 min every time. Conclusion The results indicates that SBP, DBP, and HDL-C in hypertensive patients have been effectively improved after dance therapy intervention. In addition, it is recommended to implement dance therapy for hypertensive patients with a treatment cycle of 12 weeks, and treat at least 3 times a week, with each treatment duration controlled within 60 min. Systematic Review Registration [http://www.crd.york.ac.uk/PROSPERO], identifier [CRD42024500807].